2020
DOI: 10.1101/2020.09.09.20191247
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early indirect impact of COVID-19 pandemic on utilization and outcomes of reproductive, maternal, newborn, child and adolescent health services in Kenya

Abstract: Background: The COVID-19 global pandemic is expected to result in 8.3-38.6% additional maternal deaths in many low-income countries. The objective of this paper was to determine the initial impact of COVID-19 pandemic on reproductive, maternal, newborn, child and adolescent health (RMNCAH) services in Kenya. Methods: Data for the first four months (March-June) of the pandemic and the equivalent period in 2019 were extracted from Kenya Health Information System. Two-sample test of proportions for hospital atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
102
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(138 citation statements)
references
References 19 publications
10
102
0
1
Order By: Relevance
“…However, our findings are particularly concerning because these areas already carry the majority of the global burden of maternal mortality. This finding is supported by national data from Kenya not yet formally published, 50 and we call for further investigation of maternal mortality as a matter of urgency, particularly in LMIC settings. Data from the MBRRACE-UK rapid report are reassuring; in the first wave of the pandemic (March–May, 2020), there were 16 maternal deaths (ten associated with SARS-CoV-2) of an estimated 162 344 births, corresponding to a maternal mortality rate of 9·9 per 100 000, 51 compared with a pre-pandemic rate of 9·7 per 100 000 in 2016–18.…”
Section: Discussionsupporting
confidence: 74%
“…However, our findings are particularly concerning because these areas already carry the majority of the global burden of maternal mortality. This finding is supported by national data from Kenya not yet formally published, 50 and we call for further investigation of maternal mortality as a matter of urgency, particularly in LMIC settings. Data from the MBRRACE-UK rapid report are reassuring; in the first wave of the pandemic (March–May, 2020), there were 16 maternal deaths (ten associated with SARS-CoV-2) of an estimated 162 344 births, corresponding to a maternal mortality rate of 9·9 per 100 000, 51 compared with a pre-pandemic rate of 9·7 per 100 000 in 2016–18.…”
Section: Discussionsupporting
confidence: 74%
“…[92] In India, Marie Stopes International reported serving 1.3 million fewer women with contraceptive and abortion services than expected. [93] To date, research studies have documented mixed results in terms of the impact of COVID-19 on service delivery outcomes [94-96]. Decreases in access to and use of contraceptives, antenatal care, safe abortion, and institutional delivery have been documented across different health systems and income contexts, including Kenya,[97, 98] Ethiopia,[99] Turkey,[100] Italy,[101], UK,[102] and the US.…”
Section: Resultsmentioning
confidence: 99%
“…11 In addition to the direct loss of formal education, the critical social protective functions of schools are lost with school closure, which may result in increased child labor, early marriages, adolescent pregnancies, transactional sex, genderbased violence, mental health issues, or exposures to risky behaviors such as tobacco smoking and drug use. 13,[28][29][30][31][32][33] Recently, a survey in Kampala, Uganda, reported that COVID-19 lockdowns were associated with a higher prevalence of unhealthy behaviors such as tobacco smoking/chewing, alcohol drinking, and substance use (such as marijuana). 14 Due to the increased risks of such issues and the direct deprivation of educational opportunities, many adolescents in SSA may not go back to school even after schools reopen after a crisis like the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%